Assessing changes in eco-productivity of wastewater treatment plants: The role of costs, pollutant removal efficiency, and greenhouse gas emissions - Gemar-Castillo, Germán; Gómez-Núñez, Trinidad; Molinos-Senante, María; Caballero-Fernández, Rafael Enrique; Sala-Garrido, Ramón (Elsevier, 2018)
Improving eco-efficiency of wastewater treatment plants (WWTPs) has been identified as being essential for achieving urban sustainability. Several previous papers have evaluated the eco-efficiency of WWTPs using data envelopment analysis (DEA) models. However, those models provided only a static assessment in that they ignored possible fluctuations over time within each plant. To overcome this temporal limitation, this paper evaluates dynamic eco-efficiency (changes in eco-productivity over time) of WWTPs using the dynamic weighted Russell directional distance model (WRDDM). This approach allows one to obtain an eco-productivity change index for each major component of the WRDDM model (costs, pollutants removal, and greenhouse gas emissions). Our results illustrate that although eco-productivity improved in half of the WWTPs we assessed, there was still potential for improving some eco-efficiency components. Moreover, operational costs and greenhouse gases emissions were the main drivers reducing eco-productivity. This paper demonstrates the importance of evaluating change in eco-productivity over time and in identifying the drivers associated with those changes, both of which can be used to support decision-making focused on the sustainability of WWTPs
Keywords: Plantas depuradoras de agua - Aspectos ambientales; Wastewater treatment; Eco-productivity; Dynamic eco-efficiency; Undesirable outputs; Data envelopment analysis; Luenberger productivity indicator